Extending the ARC (Ask, Record, Confirm) Technique to Enhance Real-Time Member Checking: A Case Study at Malaysia’s Transport License Department - Naharudin bin Saadan; Khairil Faizal bin Khairi; Mohd Zairul; Azuan bin Ahmad; Agoos Munalir bin Tahir (Faculty of Economics and Business, University of Muhammadiyah Makassar, 2025)
Indexed